From Crimes against Honesty to Crimes against Sexual Freedom - Rojo Gallego-Burín, Marina (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This paper is a contribution to the study of historical criminal law. Specifically, it analyzes the crimes against honesty in the Penal Codes of 1822, 1848 and 1876. In such a way that it is shown how the morality of Spanish society has been evolving during this time and how certain conducts have been penalized and others decriminalized. This is contrasted with the current Penal Code and its regulation of crimes against sexual freedom.